UPAYA GURU TAHFIDZ DALAM MENINGKATKAN HAFALAN QUR'AN SANTRI MELALUI METODE TASMI' DI PESANTREN PUTRI TAHFIDZUL QUR'AN AINUL MARDHIYYAH - Antin Nurhidayah; Happy Susanto; Muh Tajab (Universitas Muhammadiyah Ponorogo, 2022)
Abstract : This article wants to examine the problem of the method ofmemorizing the Al-Qur’an. Memorizing the Qur'an is a noble activity. Whichis currently found in tahfidz institutions. And the current challenge formemorizing the Qur'an is how to keep the Qur'an memorized. The focus ofthis research is to describe the process of implementing tasmi' inimproving the memorization of the Qur'an of students at the TahfidzulQur'an Islamic Boarding School Ainul Mardhiyyah. The object in this studyis aimed at the tahfidz teacher and the female Islamic boarding schoolstudent Tahfidzul Qur'an Ainul Mardhiyyah. The type of research used isfield research with a qualitative approach. Data collection techniques bymeans of observation, documentation and interviews. The results of thisstudy indicate that; 1) the implementation of tasmi 'is carried out in threestages, namely deposits among friends, deposits to the tahfidz teacher,and at the big halaqoh. 2) students are able to improve their memorizationof the qur'an, make their parents proud and others, with the acquisition ofcategories mumtaz, jayyid, and jayyid jiddan 3) inhibiting and supportingfactors for the implementation of tasmi' include prayer and effort, parentalsupport. So from this research, it is expected to be able to provide benefitsand good influence for other Islamic educational institutions. And it ishoped that this research will not only end here but there is still much thatneeds to be developed and improved to get the best results.Keywords: Teacher, Tahfidz, tasmi' method